The Effect of E-Procurement Risk Mitigation Strategies on Prevention of Corruption in Public Procurement in Tanzania (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study aimed to examine the effect of e-procurement risk mitigation strategies on preventing corruption in public procurement following the widespread use of bad corrupt practices in the public procurement process.Design/Methodology/Approach: The study employed a case study design, and the study population involved 140 staff working at the Ministry of Livestock and Fisheries and officials working at the Prevention and Combating Corruption Bureau (PCCB). The study employed the Yamane formula to get a sample size of 104 respondents, whereby questionnaires, an interview guide and a documentary checklist were used as data collection instruments, and during administering the tools, all respondents were responsive, which made a response rate of 100%. The collected data were analysed using descriptive statistics and inferential statistics (regression model) to determine the effect of e-procurement on preventing corruption in public procurement.Results: The results indicate that three variables out of five, namely visibility, risk control and political control, had a p-value < 0.05, which means that these variables significantly contribute to preventing corruption in public procurement under e-procurement.Research Limitation: This study was limited to two organisations, which may not achieve the principle of study generalisation on corruption in Tanzania.Practical Implication: When public procurement practitioners and suppliers use the e-procurement system effectively, it will prevent physical interactions between the parties, thus ending corruption.Social Implication: The awareness campaign and empowerment of institutions and regulatory frameworks will help end loopholes that still tempt corruption in public procurement.Originality: This paper contributes knowledge by providing first-hand information on electronic strategies for preventing corruption in public procurement.
Keywords: Corruption. e-procurement. public procurement. risk. Tanzania